Plastic material for Bluetooth headset shell and preparation method of plastic material

A composite plastic material with MoS2/PDA/TiO2 and polymer antistatic agent addresses static charge and wear/scratch issues in Bluetooth headset shells, enhancing durability and antistatic performance.

CN119119702APending Publication Date: 2024-12-13DONGGUAN SHENGMU ELECTRONICS IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411149565.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

ABS resin used in Bluetooth headset shells exhibits high insulation leading to static charge accumulation, safety hazards, and insufficient wear and scratch resistance.

Method used

A plastic material composed of polycarbonate, ABS resin, MoS2/PDA/TiO2 composite, toughening agent, lubricant, antioxidant, and polymer antistatic agent, where the MoS2/PDA/TiO2 composite enhances wear and scratch resistance, and the polymer antistatic agent improves antistatic performance by forming a conductive network and hydrophilic surface layer.

Benefits of technology

The material achieves improved wear resistance, scratch resistance, and antistatic properties, reducing dust adsorption and static charge accumulation, while maintaining toughness and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005003251100000101
    Figure BDA0005003251100000101
Patent Text Reader

Abstract

The invention relates to the technical field of plastic materials, and discloses a plastic material for a Bluetooth headset shell and a preparation method of the plastic material. The plastic material for the Bluetooth headset shell is prepared from the following raw materials in parts by weight: 30 to 50 parts of polycarbonate, 25 to 45 parts of ABS (Acrylonitrile Butadiene Styrene) resin, 5 to 12 parts of a MoS2 / PDA / TiO2 composite material, 8 to 15 parts of a toughening agent, 0.1 to 0.5 part of a lubricating agent, 0.3 to 0.8 part of an antioxidant 1010 and 0.5 to 1 part of a macromolecular antistatic agent. The material is prepared by taking ABS (Acrylonitrile Butadiene Styrene) resin and polycarbonate as matrix resin, adding an auxiliary agent and carrying out melt blending, wherein due to the addition of the MoS2 / PDA / TiO2 composite material, the wear resistance and the scratch resistance of the matrix are improved; by adding the macromolecular antistatic agent, the antistatic performance of the matrix is improved, and the adsorption of dust on the surface of the material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plastic materials, and in particular to a plastic material for a Bluetooth headset shell and a preparation method thereof. Background Art

[0002] Acrylonitrile-butadiene-styrene (ABS) resin is a thermoplastic polymer material, which is composed of three components: acrylonitrile (AN), butadiene (Bd) and styrene (St). Each of them plays a different role, giving ABS resin good impact resistance, fluidity, corrosion resistance and other advantages. Therefore, ABS resin is widely used in many fields of people's daily life, such as vehicles, color TVs, buildings, communication products and office supplies. Among them, Bluetooth headsets, as one of the communication products, are mostly made of ABS resin as their shell plastic material. However, ABS resin has high insulation, which will cause the plastic materials produced using it to accumulate a lot of static charges during use, forming static electricity, and then adsorbing a large amount of dust on the surface. At the same time, there may be safety hazards in the generation process. In addition, considering that ABS resin is used to make the shell material of Bluetooth headsets, its own wear resistance and scratch resistance are not enough to meet actual needs. Therefore, it is necessary to develop a plastic for Bluetooth headset shell with excellent wear resistance, scratch resistance and antistatic properties. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a plastic material for a Bluetooth headset housing and a preparation method thereof.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A plastic material for a Bluetooth headset shell, comprising the following raw materials in parts by weight: 30-50 parts of polycarbonate, 25-45 parts of ABS resin, 5-12 parts of MoS2 / PDA / TiO2 composite material, 8-15 parts of toughening agent, 0.1-0.5 parts of lubricant, 0.3-0.8 parts of antioxidant 1010, and 0.5-1 parts of polymer antistatic agent;

[0006] The MoS2 / PDA / TiO2 composite material is prepared by the following steps:

[0007] Step A1, grind spherical titanium dioxide for 5-10 minutes, add it into a mixture of Tirs-HCl buffer with a pH of 8.5 and deionized water to disperse it evenly, then increase the system temperature to 30°C, add dopamine and stir to react for 10-16 hours, then filter, wash and dry to obtain PDA / TiO2 material;

[0008] Step A2, adding molybdenum disulfide powder into a ball mill at a ball milling ratio of 1:5, ball milling for 2-4 hours, collecting the pre-treated molybdenum disulfide, and then mixing the pre-treated molybdenum disulfide and PDA / TiO2 material evenly, and impacting with a vortex airflow mill to obtain a MoS2 / PDA / TiO2 composite material;

[0009] Further, in step A1, the dosage ratio of spherical titanium dioxide, Tirs-HCl buffer, deionized water and dopamine is 1-3 g: 10-20 mL: 100 mL: 0.3-1 g;

[0010] Further, in step A2, the mass ratio of the pre-treated molybdenum disulfide and the PDA / TiO2 material is 1-3:1;

[0011] Furthermore, in step A2, the main engine speed of the vortex airflow mill is 1500-1700 rpm / min, and the classifier speed is 2000 rpm / min.

[0012] The polymer antistatic agent is prepared by the following steps:

[0013] Step B1, add 3-dimethylamino-1-propanol to the reactor, raise the system temperature to 45°C, slowly dropwise add 1-chlorododecane, react for 12 hours, stand for 12 hours, separate, rotary evaporate, and freeze-dry to obtain a quaternary ammonium salt product;

[0014] Step B2, dispersing the quaternary ammonium salt product and sodium hydroxide in acetone, recorded as solution 1; dispersing acrylamine and sodium hydroxide in acetone, recorded as solution 2; slowly dropping one half of solution 1 into the cyanuric chloride acetone solution, reacting at 0°C for 3-4h, then heating to 45°C, adding the remaining solution 1, maintaining the temperature for reaction for 6-8h, then raising the temperature to 90°C, dropping solution 2, continuing the reaction for 8-10h, filtering, washing, and drying to obtain the functional monomer;

[0015] Step B3, adding deionized water, sodium dodecyl sulfate, potassium carbonate, acrylic acid and ethyl acrylate into a reactor, and introducing nitrogen for 20 minutes, and then adding potassium persulfate to react for 2-3 hours to obtain polyacrylate microspheres;

[0016] Step B4, under nitrogen conditions, add ethanol, acrylic acid, functional monomers and polyacrylate microspheres into a reactor and disperse them evenly, then add azobisisobutyronitrile, and heat to 65-75° C. to react for 5-7 hours, rotary evaporate, and dry to obtain a polymer antistatic agent;

[0017] Further, in step B1, the molar ratio of 3-dimethylamino-1-propanol to 1-chlorododecane is 1:1;

[0018] Further, the cyanuric chloride acetone solution in step B2 is prepared by mixing cyanuric chloride and acetone in a dosage ratio of 0.1-0.2 mol:100 mL;

[0019] Further, in step B2, the ratio of the quaternary ammonium salt product, sodium hydroxide and acetone in solution 1 is 0.2-0.4 mol: 8-16 g: 100 mL, and the ratio of acrylamine, sodium hydroxide and acetone in solution 2 is 0.1-0.2 mol: 4-8 g: 100 mL;

[0020] Further, in step B3, the mass ratio of deionized water, sodium lauryl sulfate, potassium carbonate, acrylic acid, ethyl acrylate and potassium persulfate is 50: 0.1-0.3: 0.08-0.24: 5-10: 1-3: 0.02-0.04;

[0021] Furthermore, in step B4, the usage ratio of ethanol, acrylic acid, functional monomer, polyacrylate microspheres and azobisisobutyronitrile is 200 mL: 0.05-0.1 mol: 0.01-0.03 mol: 10-15 g: 0.2-0.4 g.

[0022] A method for preparing a plastic material for a Bluetooth headset housing comprises the following steps:

[0023] The raw materials are weighed by weight, and polycarbonate, ABS resin, MoS2 / PDA / TiO2 composite material, toughening agent, lubricant, antioxidant and polymer antistatic agent are added into a high mixer and mixed for 5-10 minutes. The mixture is then transferred into a screw extruder, melt-blended at 180-220°C, extruded into granules, and injection molded to obtain the plastic material for the Bluetooth headset shell.

[0024] Beneficial effects of the present invention:

[0025] The plastic material for the Bluetooth headset shell in the present invention is prepared by melt blending with ABS resin and polycarbonate as base resins and adding additives; wherein the addition of MoS2 / PDA / TiO2 composite material improves the wear resistance and scratch resistance of the base; the addition of polymer antistatic agent improves the antistatic performance of the base and reduces the adsorption of dust on the surface of the material.

[0026] Among the reinforcing fillers, dopamine is first used to self-polymerize on the surface of titanium dioxide to form a polydopamine film layer to synthesize the PDA / TiO2 material; then molybdenum disulfide is adhered to the surface of the PDA / TiO2 material using a vortex airflow mill to form a MoS2 / PDA / TiO2 composite material. After reinforcing fillers are introduced into the matrix, the wear resistance and scratch resistance of the matrix can be improved. This is because the comprehensive performance of MoS2 and TiO2 in the composite material can be improved through synergistic effect. Among them, TiO2, as a substrate, can exert its own excellent wear resistance and hardness properties to improve the wear resistance of the matrix, thereby improving the scratch resistance. The loading of MoS2 can utilize its graphite-like lamellar structure, the van der Waals force between layers is weak, and it is easy to slide, so that it can provide self-lubrication with less friction in the matrix, thereby effectively improving the wear resistance and scratch resistance of the matrix. In addition, the formation of the polydopamine film layer has adsorption properties that can adsorb MoS2, and also has certain elasticity and flexibility, which can prevent titanium dioxide from being destroyed by the vortex airflow pulverizer, thereby allowing MoS2 to be evenly and tightly loaded on the surface of titanium dioxide.

[0027] In the polymer antistatic agent, the tertiary amine in 3-dimethylamino-1-propanol and the chlorine in 1-chlorododecane are first reacted to synthesize a quaternary ammonium salt product containing a hydroxyl group; the hydroxyl group in the quaternary ammonium salt product, the amino group in the acrylamine and the chlorine in the cyanuric chloride are then reacted to generate a functional monomer containing a diquaternary ammonium salt structure, a triazine structure and a terminal double bond; then, under the action of an initiator, acrylic acid and ethyl acrylate are used as raw materials to synthesize polyacrylate microspheres; finally, the polyacrylate microspheres are used as cores, and acrylic acid and the functional monomers are polymerized to form a shell layer to synthesize the polymer antistatic agent. Polymer antistatic agents have excellent hydrophilicity. After being added to the matrix by melt blending, they are distributed in layers on the outside of the matrix material to form a conductive surface layer, and are distributed in "island-like" patterns inside the matrix to form a conductive network, thereby dissipating the static charge accumulated in the material. At the same time, the hydrophilic groups on the surface of the matrix (quaternary ammonium cations, carboxyl groups, etc.) can also adsorb water molecules to form a water film, further enhancing the antistatic properties of the matrix, thereby making the surface of the matrix less likely to adsorb dust. In addition, the triazine structure contained in the polymer antistatic agent can also improve the heat resistance of the matrix. In addition, the polymer antistatic agent can also use its unique core-shell structure to increase the toughness of the matrix. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] MoS2 / PDA / TiO2 composites were prepared by the following steps:

[0031] Step A1, grind 1g of spherical titanium dioxide for 5min, add 10mL of Tirs-HCl buffer solution with a pH of 8.5 and 100mL of deionized water to disperse evenly, then raise the system temperature to 30°C, add 0.3g of dopamine and stir to react for 10h, then filter, wash and dry to obtain PDA / TiO2 material;

[0032] Step A2, adding molybdenum disulfide powder into a ball mill at a ball milling ratio of 1:5, ball milling for 2 hours, collecting the pre-treated molybdenum disulfide, and then mixing 1g of the pre-treated molybdenum disulfide and 1g of the PDA / TiO2 material evenly, and impacting the mixture with a vortex airflow mill to obtain a MoS2 / PDA / TiO2 composite material. The main engine speed of the vortex airflow mill is 1500rpm / min, and the classifier speed is 2000rpm / min.

[0033] The polymer antistatic agent is prepared by the following steps:

[0034] Step B1, adding 3-dimethylamino-1-propanol to a reactor, raising the system temperature to 45°C, slowly adding 1-chlorododecane dropwise, reacting for 12 hours, standing for 12 hours, separating, rotary evaporating, and freeze-drying to obtain a quaternary ammonium salt product, wherein the molar ratio of 3-dimethylamino-1-propanol to 1-chlorododecane is 1:1;

[0035] Step B2, 0.2 mol of quaternary ammonium salt product and 8 g of sodium hydroxide are dispersed in 100 mL of acetone, recorded as solution 1; 0.1 mol of acrylamine and 4 g of sodium hydroxide are dispersed in 100 mL of acetone, recorded as solution 2; 50 mL of solution 1 is slowly added dropwise to 100 mL of cyanuric chloride acetone solution, reacted at 0° C. for 3 h, then heated to 45° C., and then 50 mL of solution 1 is added, the temperature is maintained for reaction for 6-8 h, and then the temperature is increased to 90° C., 100 mL of solution 2 is added dropwise, and the reaction is continued for 8 h, filtered, washed, and dried to obtain a functional monomer. The cyanuric chloride acetone solution is prepared by mixing cyanuric chloride and acetone in a dosage ratio of 0.1 mol: 100 mL;

[0036] Step B3, 50 g of deionized water, 0.1 g of sodium dodecyl sulfate, 0.08 g of potassium carbonate, 5 g of acrylic acid and 1 g of ethyl acrylate were added into a reactor, and nitrogen was introduced for 20 min, and then 0.02 g of potassium persulfate was added and reacted for 2 h to obtain polyacrylate microspheres;

[0037] Step B4: Under nitrogen conditions, add 200 mL of ethanol, 0.05 mol of acrylic acid, 0.01 mol of functional monomer and 10 g of polyacrylate microspheres into a reactor and disperse them evenly. Then add 0.2 g of azobisisobutyronitrile and heat to 65 °C for 5 h. Rotary evaporate and dry to obtain a polymer antistatic agent.

[0038] Example 2

[0039] MoS2 / PDA / TiO2 composites were prepared by the following steps:

[0040] Step A1, grind 2g of spherical titanium dioxide for 7min, add 15mL of Tirs-HCl buffer solution with a pH of 8.5 and 100mL of deionized water to disperse evenly, then raise the system temperature to 30°C, add 0.6g of dopamine, stir and react for 13h, then filter, wash and dry to obtain PDA / TiO2 material;

[0041] Step A2, add molybdenum disulfide powder into a ball mill at a ball milling ratio of 1:5, ball mill for 3 hours, collect the pre-treated molybdenum disulfide, and then mix 2g of the pre-treated molybdenum disulfide and 1g of PDA / TiO2 material evenly, and impact with a vortex airflow mill to obtain a MoS2 / PDA / TiO2 composite material. The main engine speed of the vortex airflow mill is 1600rpm / min, and the classifier speed is 2000rpm / min.

[0042] The polymer antistatic agent is prepared by the following steps:

[0043] Step B1, adding 3-dimethylamino-1-propanol to a reactor, raising the system temperature to 45°C, slowly adding 1-chlorododecane dropwise, reacting for 12 hours, standing for 12 hours, separating, rotary evaporating, and freeze-drying to obtain a quaternary ammonium salt product, wherein the molar ratio of 3-dimethylamino-1-propanol to 1-chlorododecane is 1:1;

[0044] Step B2, 0.3 mol of quaternary ammonium salt product and 12 g of sodium hydroxide are dispersed in 100 mL of acetone, which is recorded as solution 1; 0.15 mol of acrylamine and 6 g of sodium hydroxide are dispersed in 100 mL of acetone, which is recorded as solution 2; 50 mL of solution 1 is slowly added dropwise to 100 mL of cyanuric chloride acetone solution, and reacted at 0° C. for 3.5 h, then heated to 45° C., and then 50 mL of solution 1 is added, and the temperature is maintained for reaction for 7 h, and then the temperature is increased to 90° C., 100 mL of solution 2 is added dropwise, and the reaction is continued for 9 h, and then filtered, washed, and dried to obtain a functional monomer. The cyanuric chloride acetone solution is prepared by mixing cyanuric chloride and acetone in a dosage ratio of 0.15 mol:100 mL;

[0045] Step B3, 50 g of deionized water, 0.2 g of sodium dodecyl sulfate, 0.16 g of potassium carbonate, 7.5 g of acrylic acid and 2 g of ethyl acrylate were added into a reactor, and nitrogen was introduced for 20 min, and then 0.03 g of potassium persulfate was added and reacted for 2.5 h to obtain polyacrylate microspheres;

[0046] Step B4: Under nitrogen conditions, add 200 mL of ethanol, 0.075 mol of acrylic acid, 0.02 mol of functional monomer and 12 g of polyacrylate microspheres into a reactor and disperse them evenly. Then add 0.3 g of azobisisobutyronitrile and heat to 70°C for 6 h. Rotary evaporate and dry to obtain a polymer antistatic agent.

[0047] Example 3

[0048] MoS2 / PDA / TiO2 composites were prepared by the following steps:

[0049] Step A1, grind 3g of spherical titanium dioxide for 10min, add 20mL of Tirs-HCl buffer solution with a pH of 8.5 and 100mL of deionized water to disperse evenly, then increase the system temperature to 30°C, add 1g of dopamine and stir to react for 16h, then filter, wash and dry to obtain PDA / TiO2 material;

[0050] Step A2, add molybdenum disulfide powder into a ball mill at a ball milling ratio of 1:5, ball mill for 4 hours, collect the pre-treated molybdenum disulfide, and then mix 3g of the pre-treated molybdenum disulfide and 1g of PDA / TiO2 material evenly, and impact with a vortex airflow mill to obtain a MoS2 / PDA / TiO2 composite material. The main engine speed of the vortex airflow mill is 1700rpm / min, and the classifier speed is 2000rpm / min.

[0051] The polymer antistatic agent is prepared by the following steps:

[0052] Step B1, adding 3-dimethylamino-1-propanol to a reactor, raising the system temperature to 45°C, slowly adding 1-chlorododecane dropwise, reacting for 12 hours, standing for 12 hours, separating, rotary evaporating, and freeze-drying to obtain a quaternary ammonium salt product, wherein the molar ratio of 3-dimethylamino-1-propanol to 1-chlorododecane is 1:1;

[0053] Step B2, 0.4 mol of quaternary ammonium salt product and 16 g of sodium hydroxide are dispersed in 100 mL of acetone, which is recorded as solution 1; 0.2 mol of acrylamine and 8 g of sodium hydroxide are dispersed in 100 mL of acetone, which is recorded as solution 2; 50 mL of solution 1 is slowly added dropwise to 100 mL of cyanuric chloride acetone solution, reacted at 0° C. for 4 h, then heated to 45° C., and then 50 mL of solution 1 is added, the temperature is maintained for reaction for 8 h, and then the temperature is increased to 90° C., 100 mL of solution 2 is added dropwise, and the reaction is continued for 10 h, filtered, washed, and dried to obtain a functional monomer. The cyanuric chloride acetone solution is prepared by mixing cyanuric chloride and acetone in a dosage ratio of 0.2 mol:100 mL;

[0054] Step B3, 50 g of deionized water, 0.3 g of sodium dodecyl sulfate, 0.24 g of potassium carbonate, 10 g of acrylic acid and 3 g of ethyl acrylate were added into a reactor, and nitrogen was introduced for 20 min, and then 0.04 g of potassium persulfate was added and reacted for 3 h to obtain polyacrylate microspheres;

[0055] Step B4: Under nitrogen conditions, add 200 mL of ethanol, 0.1 mol of acrylic acid, 0.03 mol of functional monomer and 15 g of polyacrylate microspheres into a reactor and disperse them evenly. Then add 0.4 g of azobisisobutyronitrile and heat to 75 °C for 7 h. Rotary evaporate and dry to obtain a polymer antistatic agent.

[0056] Example 4

[0057] A method for preparing a plastic material for a Bluetooth headset housing comprises the following steps:

[0058] Polycarbonate (bisphenol A type polycarbonate, Mn = 15000) 30 parts, ABS resin 25 parts, MoS2 / PDA / TiO2 composite material prepared in Example 1 5 parts, toughening agent (ethylene-methyl acrylate) 8 parts, lubricant (sodium stearate) 0.1 parts, antioxidant 10100.38 parts, polymer antistatic agent prepared in Example 1 0.5 parts;

[0059] The raw materials were weighed by weight, and polycarbonate, ABS resin, the MoS2 / PDA / TiO2 composite material prepared in Example 1, a toughening agent (ethylene-methyl acrylate), a lubricant (sodium stearate), an antioxidant 1010 and a polymer antistatic agent prepared in Example 1 were added into a high mixer and mixed for 5 minutes. The mixture was then transferred to a screw extruder, melt-blended at 180°C, extruded into granules, and injection molded to obtain a plastic material for a Bluetooth headset shell.

[0060] Example 5

[0061] A method for preparing a plastic material for a Bluetooth headset housing comprises the following steps:

[0062] Polycarbonate (bisphenol A type polycarbonate, Mn = 15000) 40 parts, ABS resin 35 parts, MoS2 / PDA / TiO2 composite material prepared in Example 2 9 parts, toughening agent (ethylene-methyl acrylate) 12 parts, lubricant (sodium stearate) 0.3 parts, antioxidant 10100.5 parts, polymer antistatic agent prepared in Example 2 0.7 parts;

[0063] The raw materials were weighed by weight, and polycarbonate, ABS resin, the MoS2 / PDA / TiO2 composite material prepared in Example 2, a toughening agent (ethylene-methyl acrylate), a lubricant (sodium stearate), an antioxidant 1010 and a polymer antistatic agent prepared in Example 2 were added into a high mixer and mixed for 10 minutes. The mixture was then transferred to a screw extruder, melt-blended at 220°C, extruded into granules, and injection molded to obtain a plastic material for a Bluetooth headset shell.

[0064] Example 6

[0065] A method for preparing a plastic material for a Bluetooth headset housing comprises the following steps:

[0066] Polycarbonate (bisphenol A type polycarbonate, Mn = 15000) 50 parts, ABS resin 45 parts, MoS2 / PDA / TiO2 composite material prepared in Example 3 12 parts, toughening agent (ethylene-methyl acrylate) 15 parts, lubricant (sodium stearate) 0.5 parts, antioxidant 10100.8 parts, polymer antistatic agent prepared in Example 3 1 part;

[0067] The raw materials were weighed by weight, and polycarbonate, ABS resin, the MoS2 / PDA / TiO2 composite material prepared in Example 3, a toughening agent (ethylene-methyl acrylate), a lubricant (sodium stearate), an antioxidant 1010 and a polymer antistatic agent prepared in Example 3 were added into a high mixer and mixed for 10 minutes. The mixture was then transferred to a screw extruder, melt-blended at 220°C, extruded into granules, and injection molded to obtain a plastic material for a Bluetooth headset shell.

[0068] Comparative Example 1

[0069] This comparative example is a plastic material, which differs from Example 6 in that silicon dioxide (wear-resistant agent) is used instead of the MoS2 / PDA / TiO2 composite material prepared in Example 3, and the rest are the same.

[0070] Comparative Example 2

[0071] This comparative example is a plastic material, which differs from Example 6 in that a commercially available quaternary ammonium salt antistatic agent is used instead of the polymer antistatic agent prepared in Example 3, and the rest are the same.

[0072] The plastic materials prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:

[0073] Wear resistance test: The wear resistance test was carried out using MMW-1A configuration-controlled universal friction and wear testing machine; the friction coefficient was tested by ASTM D1894, and the sample was a 100mm×100mm 2mm thick plastic sample;

[0074] Antistatic performance test: The surface resistivity is tested according to GB / T1410-2006, using a 100mm×100mm square sample with a thickness of 2mm clamped between electrodes, and the voltage is selected to be 500V;

[0075] Tensile performance test: Tested in accordance with GB / T 1040-2006;

[0076] Scratch resistance test: Use a scratch tester to evaluate the scratch degree, use a mechanically driven scraper to scrape a line segment pattern on the plastic surface, and each scraper only scrapes once in one direction. Then use a colorimeter to measure the color deviation △E compared with the unscratched surface. The test conditions are: temperature: 23±5℃, support force: 10N, scratch speed: 1000mm / min, scraper diameter: 1mm.

[0077] The test results are shown in the following table:

[0078]

[0079]

[0080] It can be seen from the above table that the plastic material for the Bluetooth headset shell prepared by the present invention has excellent wear resistance, antistatic performance, tensile performance and scratch resistance.

[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A plastic material for a Bluetooth headset housing, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of polycarbonate, 25-45 parts of ABS resin, 5-12 parts of MoS2 / PDA / TiO2 composite material, 8-15 parts of toughening agent, 0.1-0.5 parts of lubricant, 0.3-0.8 parts of antioxidant 1010, and 0.5-1 parts of polymer antistatic agent; The MoS2 / PDA / TiO2 composite material is prepared by the following steps: Step A1, grind spherical titanium dioxide for 5-10 minutes, add it into a mixture of Tirs-HCl buffer with a pH of 8.5 and deionized water to disperse it evenly, then increase the system temperature to 30°C, add dopamine and stir to react for 10-16 hours, then filter, wash and dry to obtain PDA / TiO2 material; Step A2, adding molybdenum disulfide powder into a ball mill at a ball milling ratio of 1:5, ball milling for 2-4 hours, collecting the pre-treated molybdenum disulfide, and then mixing the pre-treated molybdenum disulfide and PDA / TiO2 material evenly, and impacting with a vortex airflow mill to obtain a MoS2 / PDA / TiO2 composite material.

2. The plastic material for a Bluetooth headset housing according to claim 1, characterized in that: In step A1, the dosage ratio of spherical titanium dioxide, Tirs-HCl buffer, deionized water and dopamine is 1-3 g: 10-20 mL: 100 mL: 0.3-1 g.

3. The plastic material for a Bluetooth headset housing according to claim 1, characterized in that: In step A2, the mass ratio of pre-treated molybdenum disulfide and PDA / TiO2 material is 1-3:1, the main engine speed of the vortex airflow mill is 1500-1700rpm / min, and the classifier speed is 2000rpm / min.

4. The plastic material for a Bluetooth headset housing according to claim 1, characterized in that: The polymer antistatic agent is prepared by the following steps: Step B1, add 3-dimethylamino-1-propanol to the reactor, raise the system temperature to 45°C, slowly dropwise add 1-chlorododecane, react for 12 hours, stand for 12 hours, separate, rotary evaporate, and freeze-dry to obtain a quaternary ammonium salt product; Step B2, dispersing the quaternary ammonium salt product and sodium hydroxide in acetone, recorded as solution 1; dispersing acrylamine and sodium hydroxide in acetone, recorded as solution 2; slowly dropping one half of solution 1 into the cyanuric chloride acetone solution, reacting at 0°C for 3-4h, then heating to 45°C, adding the remaining solution 1, maintaining the temperature for reaction for 6-8h, then raising the temperature to 90°C, dropping solution 2, continuing the reaction for 8-10h, filtering, washing, and drying to obtain the functional monomer; Step B3, adding deionized water, sodium dodecyl sulfate, potassium carbonate, acrylic acid and ethyl acrylate into a reactor, and introducing nitrogen for 20 minutes, and then adding potassium persulfate to react for 2-3 hours to obtain polyacrylate microspheres; Step B4: under nitrogen conditions, add ethanol, acrylic acid, functional monomers and polyacrylate microspheres into a reactor and disperse them evenly, then add azobisisobutyronitrile, raise the temperature to 65-75° C. and react for 5-7 hours, rotary evaporate and dry to obtain a polymer antistatic agent.

5. The plastic material for a Bluetooth headset housing according to claim 4, characterized in that: The molar ratio of 3-dimethylamino-1-propanol to 1-chlorododecane in step B1 is 1:

1.

6. The plastic material for a Bluetooth headset housing according to claim 4, characterized in that: Step B2: The cyanuric chloride acetone solution is prepared by mixing cyanuric chloride and acetone in a dosage ratio of 0.1-0.2 mol:100 mL.

7. The plastic material for a Bluetooth headset housing according to claim 4, characterized in that: In step B2, the amount ratio of the quaternary ammonium salt product, sodium hydroxide and acetone in solution 1 is 0.2-0.4 mol: 8-16 g: 100 mL, and the amount ratio of acrylamine, sodium hydroxide and acetone in solution 2 is 0.1-0.2 mol: 4-8 g: 100 mL.

8. The plastic material for a Bluetooth headset housing according to claim 4, characterized in that: In step B3, the mass ratio of deionized water, sodium dodecyl sulfate, potassium carbonate, acrylic acid, ethyl acrylate and potassium persulfate is 50: 0.1-0.3: 0.08-0.24: 5-10: 1-3: 0.02-0.

04.

9. The plastic material for a Bluetooth headset housing according to claim 1, characterized in that: In step B4, the usage ratio of ethanol, acrylic acid, functional monomer, polyacrylate microspheres and azobisisobutyronitrile is 200 mL: 0.05-0.1 mol: 0.01-0.03 mol: 10-15 g: 0.2-0.4 g.

10. The method for preparing a plastic material for a Bluetooth headset shell according to claim 1, characterized in that: The following steps are involved: The raw materials are weighed by weight, and polycarbonate, ABS resin, MoS2 / PDA / TiO2 composite material, toughening agent, lubricant, antioxidant and polymer antistatic agent are added into a high mixer and mixed for 5-10 minutes. The mixture is then transferred into a screw extruder, melt-blended at 180-220°C, extruded into granules, and injection molded to obtain the plastic material for the Bluetooth headset shell.

Citation Information

Cited By

  • Carbon nanotube-based anti-static ABS composite material and preparation method thereof

    CN119307065A

  • A kind of anti-static ABS composite material based on carbon nanotubes and preparation method thereof

    CN119307065B